Bildung, Verhalten und Lebensdauer von Plasmabullets in einem kalten Plasmastrahl bei Atmosphärendruck - Kempe, Viktor; Jovicic, Vojislav; Delgado, Antonio (Proceedings der 22. GALA-Fachtagung "Lasermethoden in der Strömungsmesstechnik", 2014)
UnivIS-Import:2015-04-17:Pub.2014.tech.ITC.stmmec.bildun

Comparison of the operational characteristics of the commercially available and newly developed porous burner flame traps for high temperature applications - Jovicic, Vojislav; Issendorff, Franz; Kempe, Viktor; Zbogar-Rasic, Ana; Delgado, Antonio (Verbrennung und Feuerung : 27. Deutscher Flammentag, 2015)
UnivIS-Import:2017-11-06:Pub.2015.tech.ITC.stmmec.compar

Experimentelle Untersuchungen zur Vergasung von Biomasse mit nicht-thermischem Stickstoff Plasma - Kempe, Viktor; Jovicic, Vojislav; Ribeiro, Mariana Almeida; Delgado, Antonio (Proceedings der 21. GALA-Fachtagung "Lasermethoden in der Strömungsmesstechnik", 2013)
Die Arbeit befasst sich mit der Untersuchung über das Potential vom Einsatz von kaltem N2 Plasma zur trockenen, energieeffizienten Vergasung von Biomasse mit dem Ziel hohe Konzentrationen an brennbarem Gas zu erzeugen. Die Konzentrationen werden mit einem Flammenionisationsdetektor (Multi-FID 14, Fa. ABB) im Abgasstrom gemessen. Vergleiche zwischen Versuchen mit gleicher Verweilzeit der Proben im Plasmastrom und variierenden Gasmengen sowie mit konstanten Volumenströmen und variierender Verweilzeit zeigen eine starke Abhängigkeit der erreichten Konzentrationen von diesen Parametern
UnivIS-Import:2015-04-16:Pub.2013.tech.ITC.stmmec.experi
Keywords: Vergasung von Biomasse; nicht-thermisches Plasma; Cold plasma; Atmorspheric plasma; Non-thermal plasma; Gasification of the biomass

Investigation of advanced temperature and thermo shock resistant ceramic components for high temperature porous burners - Jovicic, Vojislav; Zbogar-Rasic, Ana; Kempe, Viktor; Delgado, Antonio; Weiß, Roland; Dannehl, Manfred; Pritzkow, Walter E. C.; Grenz, Reinhard (Proceedings of the 10th European conference on industrial furnace and boilers, 2015)
Expansion of operation range toward higher temperatures is one of the major goals in further development of porous burner technology. This is mostly related to the fact that radiation is the most intensive mechanism of heat transfer from a porous burner to a heated object. Therefore, increase of average temperature generally leads toward higher overall efficiency. In addition, higher average temperatures are opening new possibilities for industrial application of low pollutant porous burner technology. In this study, a series of novel high-performance ceramics in various designs were investigated in short and continuous long-term experiments under different controlled combustion conditions. Materials like fiber-reinforced alumina ceramics, paper-based pre-ceramic materials and wood-based bio-ceramics were successfully characterized. Long-term combustion tests with test time of 100-500 test hours of continuous operation per test, were conducted at near stoichiometric combustion conditions using mixture of natural gas and air. Most of the tested structures and materials was for the first time tested as a porous burner component at this temperature range within the frame of here presented work. Presented results provide significant amount of useful data regarding performances and limitations of investigated novel ceramic materials and structures and also their potential for application as high temperature (1500°C and above) and thermal shock resistant porous burner components like combustion zones, flame traps or burner housing
UnivIS-Import:2017-07-10:Pub.2015.tech.ITC.stmmec.invest

Numerical analysis of heat transfer characteristics in energy piles - Zhou, Long; Masood, Rao Muhammad Atif; Jovicic, Vojislav; Zbogar-Rasic, Ana; Kempe, Viktor; Delgado, Antonio (Proceedings in Applied Mathematics and Mechanics, 2014)
UnivIS-Import:2017-12-18:Pub.2014.tech.ITC.stmmec.numeri_69

Untersuchungen zur Vergasung von Biomasse mit nicht-thermischem Stickstoff Plasma - Kempe, Viktor; Jovicic, Vojislav; Delgado, Antonio; Almeida Ribeiro, Mariana (VDI-Berichte: 26. Deutscher Flammentag "Verbrennung und Feuerung", 2013)
UnivIS-Import:2015-04-16:Pub.2013.tech.ITC.stmmec.unters